Run-time deployment and management of CoAP resources for the Internet of Things - Martín-Fernández, Cristian; Díaz-Rodríguez, Manuel; Rubio-Muñoz, Bartolomé (Sage Journals, 2017)
The continuous growth of the Internet of Things in recent years has meant it is increasingly more present, as Internet of Things scenarios such as smart homes and smart cities become part of our everyday lives. The Internet of Things devices involved can be divided into two categories in most Internet of Things scenarios. The devices can constitute a black box with specific sensors which complicates their configuration, for example, wearable products. Other Internet of Things devices can be composed through configurable microcontrollers, enabling customizable environments to be designed. However, the necessary tools and knowledge for programming and configuring microcontrollers are not accessible to everyone. This article proposes a run-time deployment and management system through the Constrained Application Protocol that bridges the gap between end users and customizable environments. With our system, end users can incorporate new sensors or actuators in their installed microcontroller without having to access and program the microcontroller board. Rather, they can manage the resources of the Constrained Application Protocol servers through an accessible and transparent Web user interface.
Keywords: Internet de los objetos; Internet of Things; Constrained Application Protocol; Constrained Application Protocol resources; Sensors and actuators; Run-time deployment